How Do We Progress? An Exploration of Alternate Explanations for BPM Capability Development - Poeppelbuss, Jens; Plattfaut, Ralf; Niehaves, Bjoern (Communications of the Association for Information Systems, 2015)
Business process management (BPM) is a topic that has received immense attention in information systems research and practice. While the existing literature comprehensively covers BPM methods, techniques, and tools, the development of BPM capability in organizations remains under-researched. Existing studies mainly present maturity models with generic sequences of distinct stages that provide a rather simplistic perspective on BPM capability progress. Taking a process theory view and drawing from organizational change literature, we elaborate on alternate templates for explaining BPM capability development. By revisiting two case studies on BPM capability development, we analyze the explanatory power of four basic theories of capability development and thus advance existing approaches to explain BPM capability progress. Our analysis shows the general applicability of these theories and points to particular advantages, disadvantages, and application conditions. Using the four basic theories as alternate templates, we also offer a much more-detailed explanation of the mechanisms behind the episodes of BPM capability progress that we observed in the two case studies. In particular, the different theoretical templates allow one to better understand the influence of internal and external contexts on BPM capability progress.